A informação patrimonial e a construção da memória: uma análise das estratégias de preservação da memória do IPHAN e do IPHAEP - Oliveira, Danielle Alves de (2013)
This research analyzes the information role in the preservation of cultural patrimony in the State of Paraíba, comparing the register ways in the agencies responsible for memory preservation, the IPHAN and the IPHAEP. With the aim to contextualize this research, a course based on the relations among information, memory and cultural patrimony is fulfilled. It points out the methodological aspects that will guide its elaboration in regard to the type and methods used in the investigation. Furthermore, it presents the route in the research development, such as the elaboration of instrumental classification, the selection of patrimony in which the study will focus on and the comparison of the historical record processes of the verified institutions. It deals with a reflection founded on the information potential in the redefinition process of memory and on the construction of identities. Moreover, it agrees with the conception of the patrimony by the symbolic and material potential of the cultural patrimonies. As result of the research, the ways of patrimony preservation and the foundation context of IPHAN and IPHAEP were discussed as well as the ruling legislations with reference to the preliminary action of cultural patrimonies. After description and comparison of documental instruments, the typologies predominant in the preservation process and the problems that involve the use of estate information were identified. The investigation corroborated the hypotheses that, despite the relevance of the information found in the historical record processes, the institutions have not perceived yet the use of these references in the process of memory redefinition.